2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--35066
|View full text |Cite
|
Sign up to set email alerts
|

Practical Skills for Students in Mechatronics and Robotics Education

Abstract: Her research interests include instructional laboratories, assessment, and student motivation. She earned a Ph.D. in systems engineering at the University of Illinois at Urbana-Champaign. During her eight years as a systems engineer at Rockwell Collins, she earned a master's degree in electrical engineering at Iowa State University. She earned a bachelor's degree in electrical engineering from Rose-Hulman Institute of Technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…The growing importance of mechatronics engineering is due to the rapid change and advancement in technology (Marzano, Martinovs & Induce, 2019). Berry, Gennert and Reck (2020) pointed out that as digital technology continues to evolve, bringing significant changes, Technical Institutions also see the importance to integrate mechatronics in their training so as to meet the demands of its learners and the forth industrial revolution. Moreover, Wu and Liu (2022) have it that module curriculums should currently be designed in a way that mechatronics teaching methods in vocational and technical Colleges meet the requirements of enterprises.…”
Section: Introductionmentioning
confidence: 99%
“…The growing importance of mechatronics engineering is due to the rapid change and advancement in technology (Marzano, Martinovs & Induce, 2019). Berry, Gennert and Reck (2020) pointed out that as digital technology continues to evolve, bringing significant changes, Technical Institutions also see the importance to integrate mechatronics in their training so as to meet the demands of its learners and the forth industrial revolution. Moreover, Wu and Liu (2022) have it that module curriculums should currently be designed in a way that mechatronics teaching methods in vocational and technical Colleges meet the requirements of enterprises.…”
Section: Introductionmentioning
confidence: 99%
“…A new robotic platform with a detailed curriculum adapted for undergraduate students, including the core subjects of robotics, especially embedded programming, must be developed to address these issues [ 15 ]. Some research showed that robotics education using embedded programming has a positive impact on students [ 16 , 17 ], and this implies that students understand the application of programming languages and electrical electronics in robotic systems.…”
Section: Introductionmentioning
confidence: 99%
“…• Standardize components: There was general consensus on the need for standard components and progress was made in identifying them. These are documented in several of the workshop publications [10,12,13]. • Share broad successes of MRE: This outcome was achieved.…”
Section: Conclusion and Lessons Learnedmentioning
confidence: 75%
“…At the conclusion of each workshop, participants completed an online survey intended to assess their expectations of, and experiences in, the workshop, as well as their plans for implementing MRE in their respective institutions. The final workshop produced another outcomea set of draft inventories and commitments by the working groups to refine and publish their findings [10][11][12][13][14].…”
Section: Approachmentioning
confidence: 99%